Advances in the study of death receptor 5 - Qiao, Xuan; Guo, Shuang; Meng, Zhiyun; Gan, Hui; Wu, Zhuona; Sun, Yunbo; Liu, Shuchen; Dou, Guifang; Gu, Ruolan (Frontiers in Pharmacology, 2025)
DR5, a receptor with the highest affinity for TRAIL under physiological conditions, selectively induces apoptosis in specific target cells such as tumor and aberrant immune cells, while minimally affecting normal cells. The TRAIL-DR5 signaling pathway is a crucial regulatory mechanism when the body responds to various exogenous interference factors, including viruses, chemicals, and radiation. This pathway plays a vital role in maintaining physiological homeostasis and in the pathological development of various diseases. Different modulations of DR5, such as upregulation, activation, and antagonism, hold significant potential for therapeutic applications in tumors, cardiovascular diseases, autoimmune diseases, viral infections, and radiation injuries. This article provides an overview of the current research progress on DR5, including the status and prospects of its clinical applications.